High sensitivity and enhanced antibiotic stewardship of the BioFire Joint Infection Panel in acute, but not chronic, prosthetic joint infection of the knee - Tsung-Li Lin; Chen-Wei Yeh; Chun-Hao Tsai; Mao-Wang Ho; Hsiu-Hsien Lin; Po-Ren Hsueh (Microbiology Spectrum)
ABSTRACT The BioFire Joint Infection (JI) Panel is a multiplex polymerase chain reaction assay developed for rapid pathogen detection in synovial fluid, particularly for suspected prosthetic joint infections (PJI). However, its diagnostic sensitivity varies by clinical context and pathogen, and the impact of prior antibiotic exposure on sample quality and PJI stewardship remains unclear. This prospective study evaluated the diagnostic performance of the Investigational Use Only JI Panel versus conventional synovial fluid culture, using Musculoskeletal Infection Society criteria and symptom onset within 3 weeks to define acute PJI. Fifty-four fresh synovial fluid samples from patients with suspected knee PJI were analyzed. In acute PJI, the JI Panel demonstrated comparable sensitivity to synovial fluid culture (80% vs. 95%; P = 0.096), while significantly reducing time to pathogen identification (mean 18.2 vs. 84.6 hours, P < 0.001), enabling earlier targeted antibiotic therapy in 83.3% of cases. Overall sensitivity across all PJI cases was moderate (50%) and significantly lower in chronic PJI (16.7%), reflecting limited panel coverage and reduced detection in prolonged infections. Prior antibiotic exposure reduced sensitivity for both methods, though not significant (P = 0.127). The absence of key pathogens such as Staphylococcus epidermidis and Cutibacterium acnes further limited diagnostic yield in chronic cases. The JI Panel offers a rapid and clinically impactful tool for diagnosing acute PJI and guiding antibiotic stewardship. However, its limitations in chronic PJI and susceptibility to antibiotic pretreatment restrict its standalone diagnostic utility. Therefore, it should complement, not replace, traditional culture methods, particularly in chronic PJI cases.IMPORTANCEThe JI Panel demonstrates high sensitivity for acute PJI but lower sensitivity for chronic infections. The ability of the JI Panel to rapidly identify pathogens in acute cases plays a significant role in improving antibiotic stewardship, ensuring timely and appropriate treatment. Given the lower sensitivity for chronic PJI, further research could focus on improving the detection of pathogens that are commonly involved in chronic infections. While the JI Panel is a promising tool for acute PJI diagnosis and supports rapid antibiotic stewardship, its limitations in chronic cases and under antibiotic exposure must be addressed to maximize its clinical utility.